Review of Géza Jeszenszky's Lost Prestige. Hungary’s Changing Image In Britain 1894–1918 - Cora, Zoltán (AMERICANA E-journal of American Studies in Hungary, 2022)
Lost Prestige. Hungary’s Changing Image In Britain 1894–1918 Géza Jeszenszky Helena History Press, 2020 422 pages ISBN 978-1-943596-17-1